2019
DOI: 10.1007/s11886-019-1166-0
|View full text |Cite
|
Sign up to set email alerts
|

The Onco-cardiologist Dilemma: to Implant, to Defer, or to Avoid Transcatheter Aortic Valve Replacement in Cancer Patients with Aortic Stenosis?

Abstract: Purpose of Review Aging is associated with an increased prevalence of both cancer and heart disease. The progression of aortic valve calcification to aortic stenosis may be accelerated by both cardiovascular risk factors and cancer treatments, such as radiotherapy with mediastinal involvement. Symptomatic aortic stenosis is occasionally diagnosed in cancer patients undergoing cardiovascular evaluation; likewise, cancer is often recognized during assessment preceding aortic valve interventions. In these complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 73 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…In daily clinical practice, some patients with severe AS and concomitant malignancy, including advanced metastatic diseases, may be more threatened by AS than by malignancy. Although TAVR may provide a >1‐year life expectancy for patients with an active malignancy, it remains difficult for multidisciplinary heart teams to make treatment recommendation for this patient population 35 . The recent OCEAN‐TAVI registry demonstrated that patients with cancer had a similar 1‐year mortality rate compared to those without 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, some patients with severe AS and concomitant malignancy, including advanced metastatic diseases, may be more threatened by AS than by malignancy. Although TAVR may provide a >1‐year life expectancy for patients with an active malignancy, it remains difficult for multidisciplinary heart teams to make treatment recommendation for this patient population 35 . The recent OCEAN‐TAVI registry demonstrated that patients with cancer had a similar 1‐year mortality rate compared to those without 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients receive significant mortality benefit with both surgical and transcatheter aortic valve replacement. 1,2 The present meta-analysis demonstrates the important differences between patient with active cancer and cancer survivors. Although short-term mortality is similar between the two groups and patients without cancer, patients with active cancer experience worse long term outcomes.…”
mentioning
confidence: 75%
“…Similar to several types of cancer, severe symptomatic aortic stenosis evolved from a terminal condition before the era of SAVR, to a single therapy condition (surgical aortic valve replacements) and today to a treatable condition with several available options. Cancer patients receive significant mortality benefit with both surgical and transcatheter aortic valve replacement 1,2 …”
mentioning
confidence: 99%
“…Cancer represents a frequent comorbidity in elderly patients requiring cardiac and non-cardiac interventions [21,22]. In these cases, the best approach is not well established because of the lack of evidence-based recommendations [23].…”
Section: Scenario 2 Metastatic Cancer and Acute Valve Regurgitation: Indication For Surgerymentioning
confidence: 99%
“…First of all, before choosing the operative approach, the Heart Team should clarify cancer prognosis with an oncologist, including appropriate cancer staging [23]. While it is reasonable that previous or remitted malignancies are not considered as contraindication to surgery, the presence of active cancer is still matter of debate.…”
Section: Scenario 2 Metastatic Cancer and Acute Valve Regurgitation: Indication For Surgerymentioning
confidence: 99%